PERUBAHAN POLA KOMUNIKASI MASYARAKAT DI ERA DIGITAL: ANALISIS PERSPEKTIF AL-QURAN TENTANG MEDIA SOSIAL DAN ETIKA KOMUNIKASI - Loso Judijanto; Rafika Nisa; Al-Amin (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2025)
This article analyses the changing communication patterns of society in the digital era through the perspective of the Quran, focusing on the use of social media and communication ethics. The digital era has changed the way people interact and share information, making social media the main tool of communication. This transformation brings significant benefits but also challenges in maintaining communication ethics in accordance with Islamic values. The Quran provides guidance on good communication, including verification of information, good manners, dissemination of useful content, and maintaining privacy. This analysis highlights the importance of applying Quranic principles in the use of social media to avoid the spread of false information, hatred and privacy violations. With the integration of Islamic values, users can create a more positive and harmonious communication environment. This study concludes that the changing communication patterns in the digital era require greater awareness and responsibility, but also offer opportunities to build a better digital community through the application of Quranic communication ethics